Mortality probabilities after revascularization and medical therapy in CAD patients under 60 years old: a meta-analysis study - Mohammad Afrouzi (SpringerOpen, 2021)
Abstract To estimate death probabilities after coronary artery bypass graft (CABG), percutaneous coronary intervention (PCI), and medical therapy (MT) in patients under 60 years old. We conducted a search systematic on PubMed, Embase, Cochrane Library, and Web of Science up to January 2021. The study included three parts. In the probabilities part (A), Comprehensive Meta-Analysis, and in the comparison parts (B and C), Review Manager was used in conducting meta-analyses. Nine studies consisting of 16,410 people with a mean age of 51.2 ± 6 years were included in the meta-analysis. Over a mean follow-up of 3.7 ± 2 years, overall mortality after CABG, PCI and MT was 3.6% (95% CI 0.021–0.061), 4.3% (95% CI 0.023–0.080) and 9.7% (95% CI 0.036–0.235), respectively. The length of follow-up periods was almost the same and did not differ much (p = 0.19). In Part B (without adjustment of baseline characteristics), 495 (4.0%) of 12,198 patients assigned to CABG died compared with 748 (4.5%) of 16,458 patients assigned to PCI (risk ratio [RR]: 0.77, 95% CI 0.50–1.20; p = 0.25). Seventy-four (3.5%) of 2120 patients assigned to CABG and 68 (4.2%) of 1621 patients assigned to PCI died compared with 103 (9.5%) of 1093 patients assigned to MT in equal follow-up periods (CABG-MT: RR 0.34; 95% CI 0.23–0.51; p < 0.002) (PCI-MT: RR 0.40; 95% CI 0.30–0.53; p = 0.02). In Part C, overall mortality after PCI in PACD patients with STEMI was higher in elderly versus young (RR 2.64; 95% CI 2.11–3.30) and is lower in men versus women (RR 0.61; 95% CI 0.44–0.83). Mortality probabilities obtained are one of the most important factors of effectiveness in the economic evaluation studies; these rates can be used to determine the cost-effectiveness of procedures in CAD patients aged < 60 years.